Effects of BST on optical and dielectric properties of Na2O-B2O3-SiO2 glasses - Intawin P. (2017)
© 2016 Trans Tech Publications, Switzerland. In this research, the effects of Ba 0.7 Sr 0.3 TiO 3 (BST) on optical and dielectric properties of Na 2 O-B 2 O 3 -SiO 2 glasses were investigated. From the study, the optically transparent glass from BST system was successfully prepared by using melt-quench method. The composition of BST used in this study are ranging between 20-60 wt.% BST. It was found that the addition of BST enhanced conductivity, but in turn reduced the percentage of transmittance in the glasses. The dielectric constant (∈ r ) of the BST/Na 2 O-B 2 O 3 -SiO 2 glasses improved with increasing the content of BST, which in turn plays an important role in controlling the properties of the BST/Na 2 O-B 2 O 3 -SiO 2 glasses.